Therapeutic techniques for scars in the maxillofacial region - حسون مراد (Latakia University Journal -Medical Sciences Series, 2023)
Scar is considered aesthetic disorder after operations of repair congenital deformities and even facial trauma operations.. These scars appear in several forms, including keloids, hypertrophic, atrophic, and atypical forms that combine the previous forms. A wide range of treatment techniques can be used to correct these scars or reduce their severity, and these techniques include surgical methods and non-surgical conservative methods to achieve appropriate results. The purpose of this article is to provide a review of the various techniques used in the treatment of scars within the maxillofacial region